2015
DOI: 10.1016/j.neulet.2014.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic spine alterations in schizophrenia

Abstract: Schizophrenia is a chronic illness affecting approximately 0.5–1% of the world’s population. The etiology of schizophrenia is complex, including multiple genes and contributing environmental effects that adversely impact neurodevelopment. Nevertheless, a final common result, present in many subjects with schizophrenia, is impairment of pyramidal neuron dendritic morphology in multiple regions of the cerebral cortex. In this review we summarize the evidence of reduced dendritic spine density and other dendritic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
132
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(141 citation statements)
references
References 91 publications
5
132
2
2
Order By: Relevance
“…Therefore, deficits in dendritic density, axonal density or both may explain the NDI deficit we observed in the hippocampus, temporal pole, and parahippocampal cortices in schizophrenia. Although conflicting findings have been reported (13), our findings of decreased hippocampal and parahippocampal neuritic density are congruent with the results of neuropathological studies of schizophrenia indicating lower microtubuleassociated protein-2 (MAP2, a cytoskeletal protein primarily located in dendrites and cell bodies) immunoreactivity mainly in hippocampus and associated areas (5,13,52). Other post-mortem studies have suggested lower prefrontal (11) and temporal(10) dendritic spine density in schizophrenia.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, deficits in dendritic density, axonal density or both may explain the NDI deficit we observed in the hippocampus, temporal pole, and parahippocampal cortices in schizophrenia. Although conflicting findings have been reported (13), our findings of decreased hippocampal and parahippocampal neuritic density are congruent with the results of neuropathological studies of schizophrenia indicating lower microtubuleassociated protein-2 (MAP2, a cytoskeletal protein primarily located in dendrites and cell bodies) immunoreactivity mainly in hippocampus and associated areas (5,13,52). Other post-mortem studies have suggested lower prefrontal (11) and temporal(10) dendritic spine density in schizophrenia.…”
Section: Discussionsupporting
confidence: 89%
“…Although it has not been investigated as thoroughly, similar deficits in MAP2, dendritic spine density, and dendritic length have been reported in bipolar disorder (11,12). However, conflicting observations, limited number of brain regions examined, small sample sizes and potential alterations during the postmortem-interval prior to tissue fixation can limit interpretation of postmortem studies (2,13). In vivo neuroimaging of these neural substrates could provide opportunity for new knowledge of the neurobiological underpinnings of severe mental illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most consistent postmortem finding in schizophrenia is reduced dendritic spine density, which has been found in several cortical regions. 47 It has been suggested that excessive pruning during adolescence may cause the dendritic spine loss. 47 Reduced somal size of pyramidal neurons and reduced density of dendrites and axon terminals in cortical layer 3 has been demonstrated in the primary auditory cortex and the auditory association cortex in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…47 It has been suggested that excessive pruning during adolescence may cause the dendritic spine loss. 47 Reduced somal size of pyramidal neurons and reduced density of dendrites and axon terminals in cortical layer 3 has been demonstrated in the primary auditory cortex and the auditory association cortex in schizophrenia. [48][49][50] Pyramidal neurons in layer 3 in the sensory cortex are involved in feedforwarding sensory signals to higher cortical areas.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Another hallmark of schizophrenia is the dysfunction of dendritic spines. Several studies reported a reduction of spine density in cortical pyramidal neurons in schizophrenia (for review, see Moyer et al 41 ). Interestingly, ultrastructural studies by Roberts et al 42 demonstrated an approximately 30% reduction of striatal spine size in schizophrenia patients compared with the control population.…”
Section: Mmp-9 In Schizophreniamentioning
confidence: 99%